2014
DOI: 10.1186/s12989-014-0062-4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of wood smoke exposure on vascular function and thrombus formation in healthy fire fighters

Abstract: BackgroundMyocardial infarction is the leading cause of death in fire fighters and has been linked with exposure to air pollution and fire suppression duties. We therefore investigated the effects of wood smoke exposure on vascular vasomotor and fibrinolytic function, and thrombus formation in healthy fire fighters.MethodsIn a double-blind randomized cross-over study, 16 healthy male fire fighters were exposed to wood smoke (~1 mg/m3 particulate matter concentration) or filtered air for one hour during intermi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
26
2
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 61 publications
5
26
2
2
Order By: Relevance
“…Our results were also consistent with two studies that measured d -Dimer (a breakdown product of fibrin that increases with coagulation) and found no association with particulate air pollutants (Delfino et al, 2008; Rückerl et al, 2006). Although we found no such association, increased P-selectin (indicator of both endothelial cell damage and platelet activation) has been previously associated with increased air pollutant concentrations (around 6–12% increases based on figures) in some (Delfino et al, 2008; Rich et al, 2012a), but not other studies (Bønløkke et al, 2014; Hunter et al, 2014). O'Toole et al (2010) reported no association between increased concentrations of PM 2.5 and PF4 (marker of platelet activation and vascular inflammation) in young adults during the winter, which is consistent with our findings.…”
Section: Discussioncontrasting
confidence: 94%
See 2 more Smart Citations
“…Our results were also consistent with two studies that measured d -Dimer (a breakdown product of fibrin that increases with coagulation) and found no association with particulate air pollutants (Delfino et al, 2008; Rückerl et al, 2006). Although we found no such association, increased P-selectin (indicator of both endothelial cell damage and platelet activation) has been previously associated with increased air pollutant concentrations (around 6–12% increases based on figures) in some (Delfino et al, 2008; Rich et al, 2012a), but not other studies (Bønløkke et al, 2014; Hunter et al, 2014). O'Toole et al (2010) reported no association between increased concentrations of PM 2.5 and PF4 (marker of platelet activation and vascular inflammation) in young adults during the winter, which is consistent with our findings.…”
Section: Discussioncontrasting
confidence: 94%
“…However, these findings were not replicated in a recent study following firefighters' exposures during a fire (Jensen et al, 2014). Similarly, a recent controlled wood smoke exposure study on firefighters did not show increased thrombosis or platelet activation (Hunter et al, 2014). In contrast, our marker of wood smoke, Delta-C, showed positive but not statistically significant associations with CRP.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Microvascular function assays were conducted 6 h after and blood samples were taken at 0, 6, and 20 hours after exposure for measures of oxidative stress and inflammation, with no obvious changes detected. Unosson and colleagues reported increased arterial stiffness in response to a comparable wood smoke exposure in health human subjects (Unosson et al , 2013), although in a follow-up study in firefighters, wood smoke exposure did not compromise vasodilatory capacity (Hunter et al , 2014). Utilizing filtrations systems to reduce indoor wood smoke PM levels in participating households in British Columbia, however, significantly improved vascular hyperemic response along with a 30% decrease in circulating C-reactive protein levels (Allen et al , 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Fires in urban settings typically give rise to very complex mixtures because of the combustion of household equipment, whereas combustion of wood can be considered as a more “clean” type of smoke. Studies on controlled exposure to wood smoke have indicated little effect on microvascular vasomotor function [ 12 , 13 ], whereas HRV was decreased [ 14 ]. To the best of our knowledge, no studies have assessed biomarkers for cardiovascular disease after controlled exposure to more complex fuels than wood, such as plastic or household materials.…”
Section: Introductionmentioning
confidence: 99%